IMPLEMENTASI GOOD CORPORATE GOVERNANCE DAN USEFULNESS INFORMASI AKUNTANSI - Hamidah Hamidah; Vordina Victomaria Sarintohe (Jurnal Proaksi, 2023)
Governance is the basis for creating the welfare of all parties in the Company, which will be reflected in the usefulness of the accounting information produced. This study aims to obtain information related to the effectiveness of governance implementation on the usefulness of accounting information. This research uses qualitative research methods with a narrative approach to gain understanding from previous studies so that a useful research conclusion can be drawn. The results of this study state that the CG structure is expected to improve the quality of accounting information, managers do have the authority to choose certain accounting policies that will have an impact on company performance, agents have opportunistic behavior. And profit management practices and information asymmetry will have an impact on the credibility of financial statements from an investor's point of view. The main finding in this study is that the implementation of proper governance will minimize the existence of profit management practices so that the accounting information generated will be more accurate.